3D Interfacing between Soft Electronic Tools and Complex Biological Tissues. Issue 3 (6th December 2020) - Li, Hegeng; Liu, Hongzhen; Sun, Mingze; Huang, YongAn; Xu, Lizhi
Abstract: Recent developments in soft functional materials have created opportunities for building bioelectronic devices with tissue‐like mechanical properties. Their integration with the human body could enable advanced sensing and stimulation for medical diagnosis and therapies. However, most of the available soft electronics are constructed as planar sheets, which are difficult to interface with the target organs and tissues that have complex 3D structures. Here, the recent approaches are highlighted to building 3D interfaces between soft electronic tools and complex biological organs and tissues. Examples involve mesh devices for conformal contact, imaging‐guided fabrication of organ‐specific electronics, miniaturized probes for neurointerfaces, instrumented scaffold for tissue engineering, and many other soft 3D systems. They represent diverse routes for reconciling the interfacial mismatches between electronic tools and biological tissues. The remaining challenges include device scaling to approach the complexity of target organs, biological data acquisition and processing, 3D manufacturing techniques, etc., providing a range of opportunities for scientific research and technological innovation. Abstract : Soft electronics enable biocompatible interfaces for physiological sensing and stimulation. However, their typical forms as 2D sheets create difficulties for integration with organs and tissues with complex 3D geometry. Recent strategies involve a transformation of soft electronic tools for building adaptive 3D interfaces with natural organs and tissues, providing advanced capabilities for biological research and therapeutic innovation.